Decision Tree Application for Renal Calculi Diagnosis - Murat Topaloğlu; Gözde MALKOÇ (International Journal of Applied Methods in Electronics and Computers, 2016)
Data mining is used for the extraction of secret, valuable and usable data from the big data and to provide strategic decision support. It created a new perspective for the use of the data in healthcare in addition to finding the answers of unexplored questions. It has gained wider usage as a method. The aim of this study is to develop a decision tree and a list of rules by data mining for the early diagnosis of renal calculi. A data set including blind and retrospective data for 150 people can diagnose with 6 attributes. A decision support system analysis was developed for the diagnosis of the patients with suspected renal calculi. Based on the results obtained and the analysis developed, a decision tree and list of rules were created to determine the factors that affect renal calculi. Weka program and J48 algorithm were used to create the decision tree and the list of rules and it was found to be 74.63% successful.